2010
DOI: 10.2298/jsc091207086z
|View full text |Cite
|
Sign up to set email alerts
|

Chelate-assisted phytoextraction: Effect of EDTA and EDDS on copper uptake by Brassica napus L.

Abstract: Chelate-assisted phytoextraction is proposed as an effective approach for the removal of heavy metals from contaminated soil through the use of high biomass plants. The aim of the present study was to compare the efficiency of the two chelators: EDTA and biodegradable EDDS in enhancing Cu uptake and translocation by Brassica napus L. grown on moderately contaminated soil and treated with increasing concentrations of EDTA or EDDS. Increasing amounts of EDDS caused serious growth suppression of B. napus and an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Based on data presented in Table 2 it can be concluded that biomass production is strongly influenced by the chelator application rate. Chelators applied in low doses, e.g., 2 mmol/kg EDDS and EDTA [111] and 3 mmol/kg GLDA [89], did not influence plant growth, but the higher concentrations significantly affected biomass production. The highest reduction in biomass (72.6%) was observed in B. juncea growing in soil treated with 10 mmol/kg EDTA and B. napus growing in soil treated with 8 mmol/kg EDDS.…”
Section: Chemically Assisted Phytoextractionmentioning
confidence: 87%
See 2 more Smart Citations
“…Based on data presented in Table 2 it can be concluded that biomass production is strongly influenced by the chelator application rate. Chelators applied in low doses, e.g., 2 mmol/kg EDDS and EDTA [111] and 3 mmol/kg GLDA [89], did not influence plant growth, but the higher concentrations significantly affected biomass production. The highest reduction in biomass (72.6%) was observed in B. juncea growing in soil treated with 10 mmol/kg EDTA and B. napus growing in soil treated with 8 mmol/kg EDDS.…”
Section: Chemically Assisted Phytoextractionmentioning
confidence: 87%
“…Numerous studies on the effect of applications of different chelating agents on metal uptake and translocation by Brassica sp. [89,[111][112][113][114][115][116] addressed the pronounced phytotoxicity which affects plant biomass production as one of the most frequently observed side effects of increased metal bioavailability. The influence of the application of different chelators on biomass reduction in cultivated Brassica species is presented in Table 2.…”
Section: Chemically Assisted Phytoextractionmentioning
confidence: 99%
See 1 more Smart Citation
“…The third is surfactants such as RH (rhamnose) [21]. To date, it has been established that numerous chelating agents exhibit different degrees of activation for lead (Pb), cadmium (Cd), copper (Cu), and zinc (Zn), and other heavy metals [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…EDTA promotes the Cd solubility as it has definite affinity and binding ability with Cd, but it did not enhances the Cd uptake in plants and consequently ameliorate its toxic effect (Romkens et al, 2002). However, most synthetic chelators like EDTA and EDDS form complexes with metals which have high stability and contaminate the groundwater (Zeremski-Skoric et al, 2010). Low-molecular-weight organic acids (LMWOA) like oxalic acid (OA) and citric acid (CA) may prove environmentally compatible alternatives for synthetic chelators because they are the part of root exudates thus acting as natural chelators (Hsiao et al, 2007).…”
Section: Introductionmentioning
confidence: 99%